Identification of components and parameters contributing to noise in transmission through the use of Shainin techniques. (19th March 2019) - Mandloi, Ramnendra; Gupta, R.C.; Tiwari, Neeraj
Growing expectation from global market poses challenges to the manufacturing industries to provide the best quality products at a competitive price. Cost of poor quality has gone up significantly with the traditional approach of controlling the quality. Traditional approaches are not very effective in solving chronic quality issues. In order to meet up the global expectation, organisation needs to explore effective and fast approaches which utilise various advanced techniques to solve chronic quality issues. This paper demonstrates the systematic use of Shainin techniques to solve chronic quality problem of noise from automotive transmission. Transmission is a complex system having many subassemblies, components and each component in turn has multiple parameters contributing to noise makes transmission noise an extremely complex multi-factorial problem. Shainin techniques known as component search and paired comparison have been used sequentially to identify components and subsequently the parameters of components contributing to the noise in the transmission.